Effectiveness of Intraoperative Neurophysiological Spinal Cord Monitoring in Lumbosacral Spine Surgery: Analysis of 6,196 Patients from Spinal Cord Monitoring Committee of the Japanese Society for Spine Surgery and Related Research - Imagama, Shiro; Segi, Naoki; Kawabata, Shigenori; Ando, Muneharu; Arakawa, Yasuo; Iwasaki, Hiroshi; Kurosu, Kenta; Nakanishi, Kazuyoshi; Tadokoro, Nobuaki; Machino, Masaaki; Kanchiku, Tsukasa; Yamada, Kei; et al. (Journal of Spine Research, 2025)
Introduction: In high-risk surgeries, those involving pathologies such as ossification of the posterior longitudinal ligament in the spine, spinal cord tumors, and spinal deformities, utilization of intraoperative neurophysiological monitoring (IONM) has been reported to be beneficial. However, efficacy of IONM for lumbosacral spinal surgery remains debated. Therefore, this study aimed to evaluate the efficacy of IONM in lumbosacral spinal surgeries in comparison with its use in cervical and/or thoracic spine surgeries.Methods: This was a multi-institutional prospective cohort study. The patients underwent spinal surgery with intraoperative neurophysiological monitoring in the hospitals of the Spinal Cord Monitoring Committee of the Japanese Society for Spine Surgery and Related Research. Patients were divided into two groups at the surgical level: 'cervical and/or thoracic' and 'lumbar and/or sacral'. Primary endpoints were sensitivity, specificity, positive and negative predictive values (PPV and NPV), and positive and negative likelihood ratios (PLR and NLR), and secondary endpoints were the incidence of postoperative motor palsy and the cutoff value of the rate of decrease of Tc-MEP amplitude in lumbar and/or sacral surgery.Results: The number of patients with cervical and/or thoracic surgery were 4,765, and those with lumbar and/or sacral surgery were 1,431. Furthermore, the sensitivity, specificity, PPV, NPV, PLR, and NLR were 77.6, 90.1, 21.1, 99.2, 7.9, and 0.2 in cervical and/or thoracic surgery, and 60.7, 95.9, 23.0, 99.2, 14.8, and 0.4 in lumbar and/or sacral surgery respectively. Specificity and PLR for lumbar and/or sacral surgery were significantly higher. Incidence of postoperative motor palsy was 3.1% (152/4,765) in the cervical and/or thoracic surgery group and 1.9% (27/1,431) in the lumbar and/or sacral surgery group. Cutoff value of the rate of Tc-MEP amplitude was 30%, with a 70% decrease compared to the baseline, and the sensitivity and specificity were 64.7% and 87.5%, respectively. The AUC was 0.69.Conclusions: Considering the substantially high specificity and PLR observed in lumbar and/or sacral surgeries, IONM can be considered effective within the context of lumbosacral spinal surgery.